2007
DOI: 10.1161/circulationaha.106.647255
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Receptor p75 Is Required in Ischemia-Induced Neovascularization

Abstract: Background-Aging is a risk factor for coronary and peripheral artery disease. Tumor necrosis factor-␣ (TNF-␣), a proinflammatory cytokine, is expressed in ischemic tissue and is known to modulate angiogenesis. Little is known about the role of TNF-␣ receptors (TNFR1/p55 and TNFR2/p75) in angiogenic signaling. Methods and Results-We studied neovascularization in the hindlimb ischemia model in young and old TNFR2/p75 knockout (p75KO) and wild-type age-matched controls. Between days 7 to 10 after hindlimb surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 42 publications
(54 reference statements)
6
109
2
1
Order By: Relevance
“…7D-F), suggesting the importance of signaling through TNFR2/ p75 in cell survival and recovery of muscle tissue after ischemia. These findings corroborate our earlier work, in which we observed that BM cells from young WT mice helped rescue limbs of 16 to 18-mo-old p75KO mice from ischemia-induced autoamputation (6), and which also validated that functional TNFR2/p75 is required in old WT tissue for efficient postischemic recovery (6).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…7D-F), suggesting the importance of signaling through TNFR2/ p75 in cell survival and recovery of muscle tissue after ischemia. These findings corroborate our earlier work, in which we observed that BM cells from young WT mice helped rescue limbs of 16 to 18-mo-old p75KO mice from ischemia-induced autoamputation (6), and which also validated that functional TNFR2/p75 is required in old WT tissue for efficient postischemic recovery (6).…”
Section: Discussionsupporting
confidence: 92%
“…1J). These histologic findings further signify our earlier observations in an identical HLI model, wherein we observed a significant increase in apoptosis in the ischemic HL tissue on d 10 in p75KO mice (6), an indication of impaired recovery in p75KO mice.…”
Section: Postischemic Recovery Is Diminished In Young P75ko Micesupporting
confidence: 90%
See 2 more Smart Citations
“…ChemR23 was not detected elsewhere in the retina under these conditions. These findings are consistent with the idea that ω-3-PUFA-derived biomediators interact with receptors on microglial cells to decrease proinflammatory cytokine production.We next examined the role of the inflammatory cytokine tumor necrosis factor (TNF)-α. Modulation of TNF-α production influences vascular growth in other systems through endothelial cell cycle regulation 17,18 . Moreover, mice lacking TNF-α have less oxygeninduced retinopathy 19 .…”
mentioning
confidence: 99%